PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR TEKNIK DASAR PASSING BOLA BASKET - ., Komang Ayu Krisna Dewi; ., I Ketut Budaya Astra, S.Pd, M.Or.; ., I Gede Suwiwa, S.Pd., M.Pd. (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan Undiksha, 2017)
Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran kooperatif Tipe Numbered Head Together (NHT) terhadap hasil belajar teknik dasar passing bola basket pada siswa kelas viii SMP Katolik Santo Paulus tahun pelajaran 2017/2018. Penelitian eksperimen menggunakan rancangan the non-randomized pretest-posttest control group design. Jenis penelitian ini merupakan penelitian semu (quasi eksperimen). Populasi yaitu seluruh siswa kelas VIII SMP Katolik Santo Paulus tahun pelajaran 2017/2018 dengan jumlah keseluruhan 36. Sampel mengunakan Total Sampling, diperoleh kelas VIII 1 yang berjumlah 18 siswa menjadi kelompok eksperimen dan kelas VIII 2 yang berjumlah 18 siswa sebagai kelompok kontrol. Penelitian ini dilakukan dengan dua kali perlakuan di luar pretest dan posttest. Data hasil belajar dikumpulkan dengan cara tes obyektif dan unjuk kerja siswa. Metode pengumpulan data berupa nilai sikap, pengetahuan dan keterampilan kemudian dianalisis mengguakan program SPSS 16.0 for Winadows. Pada kelompok eksperimen diperoleh nilai rata-rata 0,6211 dengan standar deviasi 0,13141 sedangkan pada kelompok kontrol diperoleh nilai rata-rata 0,4061 dengan standar deviasi 0,08339. Signifikan tes normalitas menggunakan Uji Kolmogorov-Smirnov, pada kelompok eksperimen dan kelompok kontrol adalah 0,200 dan 0,200. Tes signifikan homogenitas menggunakan tes Levene's Test for Equality of Variances terdapat 0,227. Angka signifikan yang diperoleh melalui uji t (t-test) adalah p=0,000. Maka dapat disimpulkan bahwa model pembelajaran NHT berpengaruh signifikan terhadap hasil belajar teknik dasar passing bola basket. Disaran kepada guru Penjasorkes agar menerapkan model pembelajaran NHT karena terbukti berpengaruh signifikan terhadap peningkatan hasil belajar siswa. Kata Kunci : Kata-kata kunci: kooperatif Tipe Numbered Head Together (NHT) hasil belajar passing bola basket This study aims to determine the effect of cooperative learning model Numbered Head Together (NHT) on the learning outcomes of basic techniques of basketball passing on students of class VIII SMP Katolik Santo Paulus in the academic year 2017/2018. The experimental study used the non-randomized pretest-posttest control group design. This type of research is a quasi-research (quasi experiment). The population is all students of class VIII SMP Catholic Saint Paul in the academic year 2017/2018 with total 36. Samples used Total Sampling, obtained class VIII 1 which amounted to 18 students into experimental group and class VIII 2 which amounted to 18 students as a control group. This study was conducted with two treatments outside the pretest and posttest. Learning result data is collected by objective test and student performance. Methods of data collection in the form of attitude, knowledge and skill values then analyzed using SPSS 16.0 for Winadows. In the experimental group obtained an average value of 0.6211 with a standard deviation of 0.13141 while in the control group obtained an average value of 0.4061 with a standard deviation of 0.08339. Significant tests of normality using the Kolmogorov-Smirnov Test, in the experimental group and the control group were 0.200 and 0.200. A significant test of homogeneity using Levene's Test for Equality of Variances was 0.227. The significant number obtained through t test (t-test) is p = 0,000. So it can be concluded that the NHT learning model has a significant effect on the learning outcomes of basic techniques of basketball passing. Suggestion to Penjasorkes teachers to apply NHT learning model because it proved to have a significant effect on the improvement of students learning outcomes.keyword : aims to determine the effect of cooperative learning model Numbered Head Together (NHT) on the learning outcomes of basic techniques of basketball passing on students of class VIII SMP Katolik Santo Paulus in the academic year 2017/2018. The experimental study used the non-randomized pretest-posttest control group design. This type of research is a quasi-research (quasi experiment). The population is all students of class VIII SMP Catholic Saint Paul in the academic year 2017/2018 with total 36. Samples used Total Sampling, obtained class VIII 1 which amounted to 18 students into experimental group and class VIII 2 which amounted to 18 students as a control group. This study was conducted with two treatments outside the pretest and posttest. Learning result data is collected by objective test and student performance. Methods of data collection in the form of attitude, knowledge and skill values then analyzed using SPSS 16.0 for Winadows. In the experimental group obtained an average value of 0.6211 with a st